The Effect of Learning Motivation and Learning Environment on Student Achievement Index (Case Study of FEB UKI Class of 2018-2019) - Cindy Sibarani; Hotner Tampubolon; Ganda Hutapea (Universitas Kristen Indonesia, 2023)
Students are academic people who have very important parts and functions in a higher education institution. The learning system is not only centered on hard skills but also soft skills. This is so that students have sufficient provisions to be able to win job competition and have bright professions. Academic achievement is a term to show an achievement or level of success related to a goal as a result of learning efforts that have been carried out by someone optimally. Achievement of student academic achievement can be influenced by internal and external aspects of each individual. To achieve maximum learning goals, one of the most influential aspects is the motivation to learn and also the learning environment. The following research aims to see how the influence of learning motivation and learning environment on academic achievement. The following research uses quantitative methods. The place where this research was carried out was at the Indonesian Christian University. In this study, data collection used questionnaires which were distributed to narasumberts. The sample in this study was 20 students from the Faculty of Economics and Business batch 2018 and 2019. The data analysis technique used in this study was multiple linear regression analysis, partial statistical test (t test), and F test. The results of the following research are (1) Learning motivation has a positive effect on student academic achievement (GPA), (2) The learning environment has a positive effect on academic achievement (GPA), (3) Simultaneously learning motivation and learning environment have an influence on academic achievement (GPA). Keywords: Motivation, Environment, Study, GPA